Estimation of Knowledge, Attitude and Prevalence of Female Sex Dysfunction in Elderly Pakistani Women - Khola Noreen; Farah Ayyaz; Lubna Meraj; Tabinda Khalid; Javara Malik; Muhammad Akram Randhawa (Journal of Rawalpindi Medical College)
Objective: The study aimed to investigate knowledge, attitude and prevalence of FSD in middle-aged and elderly ladies of our community.